Ozone Induces Oxidative Stress and Inflammation in Nasal Mucosa of Rats - Yu Zhan; Lufang Tian; Ruxin Zhang; Shaoqing Yu; Na Sun (Atmosphere)
Background: The development of the global economy has led to changes in air pollution patterns. The haze phenomenon characterized by high concentrations of particulate matter 2.5 (PM2.5) has changed to complex pollution, and photochemical pollution characterized by ozone (O3) has become increasingly prominent. Ozone pollution and its impact on human health has become an important topic that needs to be studied urgently. Objective: To investigate the effects of ozone on oxidative stress and inflammation in the nasal mucosa of a rat model. Methods: Thirty-two healthy female Sprague–Dawley rats, eight in each group, were divided into four groups using the randomized numeric table method: normal control group (NC group), normal rats with a low level of ozone inhalation exposure (NEL group, 0.5 ppm), medium ozone inhalation exposure (NEM group, 1 ppm), and high ozone inhalation exposure (NEH group, 2 ppm). The ozone inhalation exposure groups were placed in the ozone inhalation exposure system and exposed to different concentrations of ozone for 2 h each day for 6 weeks. Nasal secretion was measured, and nasal lavage and nasal mucosa were collected. Malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) activities were measured by colorimetric assay, and the nasal mucosa was analyzed by Western blot. Western blot (WB) was used to detect the expression of NF-κB p65 nuclear protein in nasal mucosa. The mRNA expression of NF-κB target genes IL-6 and IL-8 and tumor necrosis factor-α (TNF-α) was detected by real-time quantitative PCR (qRT-PCR), and the protein content of pro-inflammatory factors IL-6, IL-8, and TNF-α was detected by ELISA in serum and nasal lavage fluid. The nasal mucosa of rats was stained with hematoxylin-eosin (HE) to observe the pathological changes in the nasal mucosa. The data were analyzed by SPSS 20.0 software. Results: The amount of nasal secretion increased significantly in all groups after ozone exposure compared with that in the NC group. The MDA content of the nasal mucosa was significantly increased in the ozone-exposed group compared with the NC group, and the activity levels of SOD and GSH-Px in the nasal mucosa were lower in the ozone-exposed group than in the NC group. The mRNA expression of IL-6, IL-8, and TNF-α in the nasal mucosa of the ozone-exposed group was elevated, and the protein content of TNF-α, IL-6, and IL-8 in the nasal lavage fluid was elevated, and the content increased with the increase in ozone concentration. The expression of NF-κB p65 intracellular protein in the nasal mucosa of each ozone-exposed group was higher than that of the normal group, and the content increased with the increase in ozone concentration. Conclusions: Ozone inhalation exposure promotes oxidative stress and the release of inflammatory factors TNF-α, IL-6, and IL-8, leading to pathological damage of the nasal mucosa, the degree of which increases with increasing concentration. This pathological process may be related to the activation of the transcription factor NF-κB by ozone in the nasal mucosa of rats, which increases the expression of its target genes.